1991
DOI: 10.1099/0022-1317-72-6-1323
|View full text |Cite
|
Sign up to set email alerts
|

Fusion activity of flaviviruses: comparison of mature and immature (prM-containing) tick-borne encephalitis virions

Abstract: The fusion activity of flaviviruses [tick-borne encephalitis (TBE) virus and Japanese encephalitis virus] was assessed by inducing fusion from without of C6/36 mosquito cells with purified virus preparations. Membrane fusion and polykaryocyte formation was observed only after incubating the viruses at acidic pH. Two groups of monoclonal antibodies reacting with distinct non-overlapping antigenic domains on the TBE virus protein E inhibited fusion from without. One of these domains contains the most highly cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
156
1
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 33 publications
5
156
1
2
Order By: Relevance
“…However, a number of other studies have reported the secretion of DENV RSPs from mammalian cells expressing the DENV prM and E genes, either transiently (Fonseca et al, 1994;Raviprakash et al, 2000) or stably (Konishi & Fujii, 2002;Konishi et al, 2003). Previous studies have determined that furin-mediated cleavage of prM was necessary to activate the full fusogenic potential of flaviviruses (Guirakhoo et al, 1991(Guirakhoo et al, , 1992Stadler et al, 1997). In our experiments, the levels of secreted prM were high relative to intracellular prM levels, both from virally infected C6/36 cells and from pSVprM-E-transfected COS cells, suggesting that prM processing was impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of other studies have reported the secretion of DENV RSPs from mammalian cells expressing the DENV prM and E genes, either transiently (Fonseca et al, 1994;Raviprakash et al, 2000) or stably (Konishi & Fujii, 2002;Konishi et al, 2003). Previous studies have determined that furin-mediated cleavage of prM was necessary to activate the full fusogenic potential of flaviviruses (Guirakhoo et al, 1991(Guirakhoo et al, , 1992Stadler et al, 1997). In our experiments, the levels of secreted prM were high relative to intracellular prM levels, both from virally infected C6/36 cells and from pSVprM-E-transfected COS cells, suggesting that prM processing was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of immature DENV and YFV particles obtained by cryo-EM reconstruction revealed pronounced spikes, each comprising three prM/E heterodimers projecting from the virion surface (Zhang et al, 2003b). The prM proteins associate to cap each spike, covering a fusion peptide located in the E protein, a mechanism that is believed to prevent premature fusion during virion transport through the low-pH environment of the secretory pathway (Guirakhoo et al, 1991(Guirakhoo et al, , 1992Heinz et al, 1994). Prior to or during release of the infectious virus from cells, the host enzyme furin cleaves the prM protein (Stadler et al, 1997), a process that is believed to dissociate the prM/E heterodimer, resulting in rearrangement of the E proteins into tightly packed dimers on the surface of the mature virus particle .…”
mentioning
confidence: 99%
“…Recent studies on selected flaviviruses suggest that the processing of preM to M is a pH-dependent event, which takes place in post-golgi acid vesicles. This proteolytic event may be necessary for fusion of virus with susceptible cells (43,94). Some flaviviruses may, however, be released from infected cells predominantly in the immature form (43).…”
Section: P R O C E S S I N G O F T H E F L a V I V I R U S P O L Y P mentioning
confidence: 99%
“…This proteolytic event may be necessary for fusion of virus with susceptible cells (43,94). Some flaviviruses may, however, be released from infected cells predominantly in the immature form (43). Additional factors may be involved in the cellular release of the immature flavivirions.…”
Section: P R O C E S S I N G O F T H E F L a V I V I R U S P O L Y P mentioning
confidence: 99%
“…For a long time the role of prM antibodies during flavivirus infection was not understood, as numerous functional studies revealed that immature prM-containing flavivirus particles are non-infectious (Elshuber & Mandl, 2005;Stadler et al, 1997). Indeed, studies on TBEV, DENV and WNV have shown that cleavage of prM to M is required to activate the membrane-fusion machinery of the virus (Guirakhoo et al, 1991;Moesker et al, 2010;Stadler et al, 1997;Zybert et al, 2008). Interestingly, however, we recently observed that prM antibodies bind to fully immature DENV particles and facilitate cellular entry through Fc receptor and fusion in a furin-dependent manner (Rodenhuis- Zybert et al, 2010).…”
mentioning
confidence: 99%